An Evaluation of the Methodological Underpinnings of a Laboratory Paradigm for the Study of Sexual Violence. Issue 23 (December 2022) - Angelone, D. J.; Mitchell, Damon; Yucel, Ebru; Davis, Kelly Cue; George, William H.
Ethically constructed laboratory paradigms can provide behaviorally based opportunities to study sexual violence as an addition to questionnaires. One such paradigm invites male participants to watch and show sexual materials to a female confederate as an analog of sexual perpetration. However, there has been inconsistency in the confederate's presentation, such that she either expresses a dislike of sexual material or her preferences are omitted. Some researchers have also questioned whether an expressed dislike is analogous to an expressed nonconsent. As such, the primary goal of the current study was to determine whether confederate expressions of dislike, nonconsent, or the omission of a preference, differentially affect male participants' behavior within a well-established paradigm. That is, we attempted to clarify the appropriate methodology for future researchers (i.e., the validity of the paradigm) and determine the impact of such a situational manipulation on laboratory-based sexual violence. Participants were 276 adult men, who were randomly assigned to one of three conditions: (1) dislike, (2) nonconsent, or (3) said nothing (the omission of a preference) and then asked to show a brief video clip to the female confederate who expressed these preferences. Overall, exposure to experimental condition predicted sexual video-showing over and above that of social desirability, hostile sexism (HS), and sexual violence history, suggesting that situational variables can play a significant role in laboratory-based sexual violence. Greater HS was associated with greater likelihood of sexual video-showing in the nonconsent condition relative to the dislike condition. Sexual video-showing was most frequent in the said nothing condition. In sum, researchers should be mindful of the confederate expression (or lack thereof) of preferences for sexual materials when using the sexual imposition paradigm.